Intention to Purchase Electric Passenger Vehicles Among Drivers in Thailand: A Structural Equation Modeling Analysis - Promphat, Santi (Animo Repository, 2019)
Electric passenger vehicles are still in the early stage of research and development in Thailand, but domestic researchers are already keen to know about the variety of factors that would have a potential to influence the intention of Thai drivers to buy the said vehicles. Using structural equation modeling analysis, this study examined the direct and indirect effects of attitude, external environment, marketing mix, subjective norms, and customer perception on purchase intention. Data were obtained from a sample of 650 Thai licensed drivers who were randomly selected and interviewed at 367 car service centers located across Bangkok. Results reveal that 52.3% of the purchase intention of Thai drivers are explained by the five-factor model. However, of the five factors, the most significant is subjective norms, followed by the marketing mix and attitude. Attitude, which lies at the heart of purchase intention, is predicted most significantly by the external environment. The findings suggest that Thailand’s concerted efforts on electric passenger vehicles would have to be carefully designed such that the relevant external environment, subjective norms, marketing mix, and attitude would all be directed to influence the purchase intention of local drivers positively. The model needs further validation among a broader sample of Thai drivers.